EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS III INDONESIAN SUBJECT THROUGH PROBLEM BASED LEARNING MODELS - Syarifah Tri Suciati; Isna Ida Mardiyana; Astien Diena Koesmini; Rukmiyati Rukmiyati (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Based on the results of a preliminary study conducted on class III students at Mlajah 2 Elementary School, it was found that most of the students had low learning outcomes in the Indonesian subject. This is due, in part, because students tend not to focus during learning. This lack of student focus can be caused by several factors, for example the use of inappropriate learning models. The purpose of this study was to see an increase in student learning outcomes in the Indonesian subject through a problem-based learning model. This research is a type of classroom action research with the model of Stephen Kemmis and Robbin Mc. Taggart. Data were collected by interview, observation, tests, and documentation techniques, then analyzed using a qualitative-quantitative approach. The results showed that there was an increase in the number of students completing from pre-cycle to cycle II. At the pre-cycle stage, the number of students passing only reached 44%. This figure then increased in cycle I, namely to 77% and 87% in cycle II. The results of this study indicate that using a problem-based learning model can improve student learning outcomes in the Indonesian Language Subject.